Using Mini-Games to Teach Cyber Issues to Social Science Students. (22nd December 2021) - Whyte, Christopher
Abstract: This essay outlines a set of mini-games designed to more effectively allow political science instructors, particularly in International Relations, teach basic principles and concepts associated with digital insecurity and cyber conflict. This topic, increasingly significant in IR syllabi in recent years, is in many cases considered with trepidation or uncertainty about the significance of different subjects within that might be covered. As a result, instructors often fall back on discussion of paradigm examples and fail to teach the underlying principles of function and logical design that give students insight into the security dynamics of the digital domain. Without such instruction, students in political science are less likely to act on interest in digital issues or science, technology and society topics more broadly. The games suggested herein are resources aimed at easing the challenge of providing such instruction and are accompanied by elaboration on student responses from three years of their use. These mini-games are extremely successful and, more importantly, simple and versatile enough that their incorporation in both introductory and intermediate IR syllabi is easy.